+0  
 
+5
94
2
avatar

3a divided by 5 - 6 = 3

Guest Feb 25, 2017
Sort: 

2+0 Answers

 #1
avatar+4157 
+1

\(\frac{3a}{5-6} = 3 \\ \frac{(5-6)3a}{5-6}=3(5-6) \\ 3a=3(-1) \\ a=-1\)

 

If you meant - 6 not in the denominator it's:

 

\(\frac{3a}{5}-6 = 3 \\ \frac{3a}{5}-6+6 = 3 + 6 \\ \frac{3a}{5} = 9 \\ \frac{(5)3a}{5} = (5)9 \\ 3a=45 \\ 3a/3=45/3 \\ a=15\)

hectictar  Feb 25, 2017
 #2
avatar+6765 
0

\(\dfrac{3a}{5}-6 = 3\\ \dfrac{3a}{5}=9\\ \dfrac{a}{5}=3\\ a=15\)

MaxWong  Feb 25, 2017

14 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details